Effects of soil ingestion on nutrient digestibility and rumen bacterial diversity of Tibetan sheep. (December 2022) - Xin, Guosheng; Ge, Cuicui; Gao, Qiaoxian; Zhang, Juan; Nie, Yumin; Yang, Yi; Zhang, Dongtao; Li, Hao; Ren, Yali
Abstract: Tibetan sheep ( Ovis aries ) are the most numerous livestock in Tibet Plateau pasture ecosystem and have strong ecological adaptability. In the natural grazing system, soil as a natural nutrient carrier and involuntarily or intentionally ingested by Tibetan sheep contribute as an important feed approach. However, quantifying the dosages of soil ingestion for the Tibetan sheep still needs to be clarified. This study aims to characterize nutrient digestibility and rumen bacterial communities by Tibetan sheep in response to different levels of soil ingestion. Thirty sheep were selected and divided into five treatments with soil ingestion (0%, 5%, 10%, 15%, and 20%). The conclusion demonstrated that soil ingestion improved the dry matter digestibility (59.3–62.97%), ether extract (59.79–67.87%) and crude protein (59.81–66.47%) digestibility, particularly 10% soil ingestion has highest nutrient digestibility. The rumen fermentation environment adjusted after soil ingestion by improvement of pH, ammonia nitrogen and volatile fatty acids. Appropriate soil ingestion reduced the bacterial diversity ranged from 946 to 1000 OUTs as compared control (1012), and the rumen bacterial community dominant by typical fiber digestion associated Firmicutes (47.48–53.56%), Bacteroidetes (34.93–40.02%) and Fibrobacteres (4.36–9.27%). Especially, the highest digestible feed capacity and stronger environment adaptability present in 10% soil ingestion Tibetan sheep. Overall, soil ingestion stimulates rumen metabolism by creating a favorable environment for microbial fermentation, improved bacterial community abundance associated with cellulose and saccharide degradation, contribute nutrient digestibility and growth performance of Tibetan sheep. Graphical abstract: Image 1 Highlights: Soil ingestion improved nutrient digestibility and growth performance of Tibetan sheep. The rumen bacterial dominant by Firmicutes (47.48–53.56%) and Bacteroidetes (34.93–40.02%). Soil ingestion improved rumen ammonia nitrogen and volatile fatty acids. Soil ingestion enhanced potassium, calcium and sodium content (5.26, 1.27 and 136.93 mmol/L). The amendment of 10% soil into the Tibetan sheep diet is recommended.